Contribution of Fluorescence Techniques in Determining the Efficiency of the Non-thermal Plasma Treatment - Carré, Gaëlle; Charpentier, Emilie; Audonnet, Sandra; Terryn, Christine; Boudifa, Mohamed; Doliwa, Christelle; Belgacem, Zouhaier Ben; Gangloff, Sophie C.; Gelle, Marie-Paule (Frontiers in Microbiology, 2018)
We have recently developed a Non-Thermal Plasma (NTP) equipment intended to sterilize fragile medical devices and maintain the sterile state of items downstream the treatment. With traditional counts on agar plate a six log reduction of Staphylococcus aureus viability was obtained within 120 minutes of O2, Ar or N2 NTP treatments. However to determine the best NTP process, we studied the different physiological states of S. aureus by flow cytometry (FC) and confocal laser scanning microscopy (CLSM) focusing on the esterasic activity and membrane integrity of the bacteria. Two fluorochromes, DCFDA and propidium iodide were used in order to distinguish three sub-populations: metabolically active, permeabilized and damaged bacteria that can be in the viable but nonculturable state. FC and CLSM highlight that O2 and Ar NTP treatments were the most attractive processes. Indeed, a 5 minutes of Ar NTP generated a high destruction of the structure of bacteria and a 120 minutes of O2 NTP treatment led to the higher decrease of the total damaged bacteria population. SEM observations showed that in presence of clusters, bacteria of upper layers are easily altered compared to bacteria in the deeper layers. In conclusion, the plate counting method is not sufficient by itself to determine the best NTP treatment. FC and CLSM represent attractive indicator techniques to select the most efficient gas NTP treatment generating the lowest proportion of viable bacteria and the most debris.